CHARACTERISTICS OF PRETERM WITH SIGHT THREATENING RETINOPATHY OF PREMATURITY - Hanif, Muhammad; Ariff, Shabina; Ansar, Aisha; Ahmed, Khabir; Hussain, Ali Shabbir (Journal of Ayub Medical College Abbottabad, 2020)
Background: Retinopathy of prematurity (ROP) is a preventable and treatable vaso-proliferative disorder of the retina which develops mostly in preterm babies. It is a leading cause of childhood blindness and more common in under developed countries. Prevalence of the severe ROP is 7.7% in Pakistan. We reviewed the characteristics of preterm babies with severe ROP to evaluate the predictors of sight threatening ROP. Methods: Our study was conducted at the NICU of Aga Khan University Hospital which is a tertiary care private sector hospital in Karachi. Ninety-seven cases of severe ROP were found out of which 83 cases were enrolled. Data on determinants for ROP were collected including gestational age, birth weight, weight gain at two and four weeks, h/o blood transfusion, supplementary oxygen, presence of PDA and its treatment. Data analysis was done by using SPSS version 20.0 Results: Frequency of severe ROP in our cohort was 5.95%. Mean gestational age for severe ROP was 28.27±1.79 and mean birth weight was 1069.16±271.71 grams. The overall mean weight gain per week in these babies was 94.62±75.64 grams. Supplementary oxygen was provided in almost 100% (82/83 cases) of cases. Surfactant was given to 56.6 % babies. PDA was found in 23 cases out of which 19 were treated by medical therapy whereas surgical treatment was done in 4 cases. Conclusion: Severe Retinopathy of prematurity was directly correlated with low birth weight, and gestational age. An average, weight gain in four weeks was lower in ROP babies (94.62±75.64 grams) than the recommended weight gain (WHO recommended 140-210 gm per week). This could be associated with the development and severity of ROP requiring treatment. Therefore, a prospective case control study is required to further identify risk factors associated with the above cohort. Screening and follow up of all such babies according to the international criteria is the need of the day. Keywords: Child health; Retinopathy of prematurity; Low birth weight; Gestational age; Childhood blindness; Risk factors; weight gain